International Conference on Space Optics — ICSO 2018 2019
DOI: 10.1117/12.2535929
|View full text |Cite
|
Sign up to set email alerts
|

Active correction system of a deployable telescope for Earth observation

Abstract: Deployable optics can bring major cost reductions to the field of Earth Observation. One of the key challenges in the development of a deployable optical system, however, is making sure that it can meet its performance targets following its deployment. In this paper, a novel active correction system for a deployable telescope is described. The correction system co-aligns and phases the primary mirror segments and subsequently corrects remaining aberrations using a deformable mirror. A novel phasing sensor call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…From that, the top-down misalignment budgets were derived and presented in Ref. 97. In addition to the optical analysis, several Master of Science theses have been published by the TU Delft, [98][99][100][101][102] detailing the evolution of the mechanical design from the first iteration by Dolkens to the latest developments reported by Dolkens et al 103 The DST, as shown in Fig.…”
Section: Deployable Space Telescope (Tu Delft)mentioning
confidence: 99%
See 1 more Smart Citation
“…From that, the top-down misalignment budgets were derived and presented in Ref. 97. In addition to the optical analysis, several Master of Science theses have been published by the TU Delft, [98][99][100][101][102] detailing the evolution of the mechanical design from the first iteration by Dolkens to the latest developments reported by Dolkens et al 103 The DST, as shown in Fig.…”
Section: Deployable Space Telescope (Tu Delft)mentioning
confidence: 99%
“…Successful operation of the system relies on three layers of increasingly strict tolerances. 97 The deployment mechanism should be accurate enough to reach a coarse alignment in the micron range. The system is then actuated to a nominal position in the order of λ∕20, with short WFE jitter disturbances kept below the order of λ∕100, with λ being the diffraction-limited wavelength of the telescope.…”
Section: Deployable Space Telescope (Tu Delft)mentioning
confidence: 99%
“…Figure 1 shows us the basic idea of a small deployable telescope in the Fresnel configuration [11]. It has two drawbacks: the segments' positions and shapes.…”
mentioning
confidence: 99%
“…We assumed that the initial errors in the tip, tilt, and piston, were up to ±1 mm, and the working wave length was in the visible, ~0.5 µm. Now we employed a method akin to optical coherence tomography (OCT): we scanned one segment and observed the combined PSF of all segments, to see when it varied in intensity [1,11,15]. Such a variation meant that fringes ran through the image in focus.…”
mentioning
confidence: 99%
See 1 more Smart Citation